The Power of Interest Coverage and Free Cash Flow in Enhancing Firm Value - Rosdiana, Rosdiana; Paramitra, Yuaniko (Research of Finance and Banking, 2025)
This research aims to analyze the effects of the interest coverage ratio and free cash flow on the value of PT Indofood CBP Sukses Makmur Tbk. The data are analyzed using multiple linear regression on secondary data in SPSS 16, sourced from the financial reports of PT Indofood CBP Sukses Makmur Tbk for the period 2017–2024. The results of the F-test indicate that both the interest coverage ratio and free cash flow have a significant effect on the firm's value. The t-test results indicate that the Interest Coverage Ratio (ICR) has a significant negative effect on the firm's value. In contrast, Free Cash Flow (FCF) has a significant positive effect. The findings of this study provide important implications for firm management and investors. For management, the results emphasize the need to balance debt repayment capacity with investment in growth-oriented projects to avoid negative market perceptions and sustain long-term firm value. For investors, the findings highlight that Free Cash Flow serves as a strong signal of financial flexibility and growth potential, providing a key indicator for investment decisions in capital-intensive industries such as food and beverages.